Protocol for unifying cross-chain liquidity on polkadot - Valaštín, Viktor; Morháč, Dušan; Košťál, Kristián; Kotuliak, Ivan (Frontiers in Blockchain, 2024)
Liquidity is critical for a healthy and thriving blockchain ecosystem, enabling value exchange between participants. However, achieving unified liquidity across heterogeneous blockchain platforms remains challenging due to disparities in architecture, virtual machines, and asset management logic. These disparities force assets to be wrapped into other formats to ensure compatibility with underlying systems, thus fragmenting liquidity into multiple pools. This paper proposes LiquiSpell, a novel protocol that aims to unify liquidity across multiple parachains within the Polkadot ecosystem. By leveraging the cross-chain message passing (XCMP), LiquiSpell introduces the concept of a universal transaction that can be constructed to be compatible with any parachain, regardless of its underlying architecture or asset management pallet. This approach overcomes the obstacles posed by the diverse nature of parachains, enabling seamless asset sharing and enhancing cross-chain interoperability. The proposed solution mitigates liquidity fragmentation within the Polkadot ecosystem. It presents a framework that can be extended to other multichain environments outside Polkadot. Ultimately, LiquiSpell aims to foster a thriving ecosystem by facilitating the introduction of new assets and increasing overall liquidity, thereby driving innovation and adoption within the decentralized finance (DeFi) landscape.